The evolution of water culture in Malta: an analysis of the changing perceptions towards water throughout the ages - Sapiano M.; Micallef P.; Attard G.; Zammit M.-L. (Water culture and water conflict in the Mediterranean area, 2008)
Since time immemorial, the provision of water in sufficient quantities has been one of the most pressing national problems. This paper will try to analyze the changing public perceptions towards water and its use throughout the last two millennia, through the development of a correlation between the prevalent social and economic changes experienced. To this end, the background social and environmental conditions characterizing four distinct periods in Maltese history will be analyzed, in order to determine their effects on the popular perception to water.
1. MELIA Workshop Water Culture and Water Conflict, 2007/11/22-25, Nabeul-Médenine (Tunisia)